2020
DOI: 10.1002/psb.1849
|View full text |Cite
|
Sign up to set email alerts
|

“Alexa… what pills do I need to take today?”

Abstract: Can personal digital assistants such as Amazon Alexa help to improve patients’ adherence to their medicines? Here, the authors discuss the potential and the limitations of this technology, and describe their pilot study in patients with diabetes and other underlying health conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 1 publication
1
5
0
Order By: Relevance
“…Res. Public Health 2021, 18, 1113 2 of 13 cost, may foster older adults' abilities to manage chronic conditions [12][13][14] and support independent living [13][14][15][16][17] and may reduce actual or perceived caregiver burdens [14,16]. Research findings suggest that many older adults are interested in learning about and using technology to promote their independence, function, and ability to age in place [5,12,16,17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Res. Public Health 2021, 18, 1113 2 of 13 cost, may foster older adults' abilities to manage chronic conditions [12][13][14] and support independent living [13][14][15][16][17] and may reduce actual or perceived caregiver burdens [14,16]. Research findings suggest that many older adults are interested in learning about and using technology to promote their independence, function, and ability to age in place [5,12,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers in the United Kingdom placed VHAs in the residences of 30 older adults with chronic conditions. Preliminary results indicated that the VHAs promoted independent living [12], mental health [12], and chronic condition management behaviors such as medication adherence [13]. Chronic conditions require management and are often associated with functional impairments, leading to the need for support from family and friends (i.e., informal/formal caregivers) to enable continued aging in place [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Research findings indicate that voice-activated virtual home assistants (VHAs) such as Amazon Echo and Google Home devices may be useful in promoting medication adherence [ 22 , 23 ]. Amazon currently holds more than 70% of the market share of VHAs [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, no study has specifically evaluated users’ perceptions of their effectiveness. Beaney et al [ 22 ] suggested that Amazon’s medication reminder skill could benefit from more development. For example, it does not have a feature for as-needed medications, that is, those not taken on a regular schedule [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation